Pengaruh Pembelajaran Berbasis Kelompok terhadap Kemampuan Sosial Siswa di TK Tunas Karya: The Effect of Group-Based Learning on Students' Social Skills at Tunas Karya Kindergarten - Damsiatang Damsiatang; Nur Azizah (ITScience (Information Technology and Science), 2026)
This research aims to determine children's social abilities before and after implementing group-based learning and to test the effect of group-based learning on the social abilities of group B children at Tunas Karya Kindergarten. The research uses a quantitative approach with the Pre-Experimental method through a One-Group Pretest-Posttest design. The research subjects were 23 children aged 5-6 years who were selected using purposive sampling techniques. Data were collected through observation using a checklist sheet that had met validity and reliability tests. Data analysis was carried out using descriptive statistics to describe children's social abilities, a paired-samples t-test to test differences in scores before and after treatment, and N-Gain to determine the level of effectiveness of the intervention. The results showed that the average social skills of children increased from 24.52 in the Starting to Develop category to 39.39 in the Very Well Developing category. Improvements also occurred in every aspect of social skills, namely cooperation from 8.17 to 13.17, empathy from 7.96 to 12.83, and positive social interaction from 8.39 to 13.39. The results of the hypothesis test show that the calculated t value of 21.95 is greater than the t table of 1.717 with a significance value of 0.000 (p<0.05), so that group-based learning has a significant effect on children's social abilities. The N-Gain value of 0.62 indicates that the effectiveness of the intervention is in the medium category. These findings indicate that group-based learning can create more active interactions and increase children's opportunities to work together, share, communicate, and respect peers, making it worth considering as a learning strategy for developing the social skills of young children in the kindergarten environment.